RP-UPLC method development and validation for simultaneous estimation of Etoricoxib and Thiocolchicoside in tablets - Sanjay Shesha Shetgar, Ramadevi Dharmasoth, Bandlamudi Mallikarjuna Rao, Basavaiah Keloth (Journal of Applied Pharmaceutical Science, 2022)
A sensitive, accurate, stability-indicating, and rapid Reversed Phase (RP)-ultra performance liquid chromatography (UPLC) method was developed and validated for the simultaneous estimation of Etoricoxib and Thiocolchicoside in a tablet formulation as there are no published literature for the short run time using the UPLC method. Etoricoxib, a nonsteroidal inflammatory drug relieves pain and swelling of the skeleton muscles, whereas Thiocolchicoside, a muscle relaxant is used as an add-on treatment for pain due to permanent tightening of muscles. The developed method with Waters Acquity UPLC with Hibar, C18 column and Acquity Tunable Ultra Violet (TUV) detector at 256 nm has a short run time of less than 3 minutes. Linearity and range were established between 25% and 150% levels with R2 value of 0.999 for both Etoricoxib and Thiocolchicoside drugs. Precision and accuracy was within the relative standard deviation of 2% for both the drugs. Recovery of 99.71% and 99.90% was achieved for Etoricoxib and Thiocolchicoside, respectively. The limits of detection and quantitation were obtained from regression equations and observed to be 0.04 and 0.64 µg/ml for Thiocolchicoside and 0.11 and 1.93 µg/ml for Etoricoxib, respectively. Degradation studies of the tablet formulation under stress conditions of oxidation, acid, base, temperature, water, and UV light indicated that the method is specific with no interference from any of the potential impurities that could form over the shelf life. The developed RP-UPLC method, which is sensitive, accurate, stability–indicating, and rapid, makes it an efficient tool in routine laboratory testing, as well as cleaning residue studies, for active pharmaceutical ingredients and formulations.
Keywords: Accuracy, Etoricoxib, rapid, RP-UPLC, simultaneous, Thiocolchicoside